SEPSIS IN INTENSIVE CARE UNITS: AN INTEGRATIVE REVIEW OF RISK FACTORS - Semaan, Karime Macedo (2023)
Sepsis, a serious syndrome triggered by an uncontrolled body response to an infection, is one of the main causes of morbidity and mortality in Intensive Care Units around the world. Several factors increase the risk of developing sepsis in patients in these units, requiring attention and preventive measures. This article consists of an integrative review, which aims to discuss the risk factors of sepsis in Intensive Care Units, through considerations about sepsis and sepsis in Intensive Care Units, with the aim of expanding students' knowledge and professionals in the field on the topic in question. This is an integrative review, in which a search was carried out in the databases. In general, the increase in the incidence of sepsis is mainly related to the aging of the population, exposure to invasive procedures, compromised immunity, use of immunosuppressive medications, alcoholism, malnutrition, diabetes mellitus and infections with antibiotic-resistant bacteria. Sepsis remains a significant challenge in Intensive Care Units, with several risk factors contributing to its development and worsening. Understanding these elements is crucial to early identify patients in situations of greater vulnerability, implement effective preventive and therapeutic measures, aiming to reduce the incidence and impacts of this serious condition. Careful control and management of these risk factors can significantly improve the prognosis and survival of patients with sepsis in Intensive Care Units.